Dentoalveolar radiation dose following IMRT in oropharyngeal cancer—An observational study. (12th February 2021) - Patel, Vinod; Humbert‐Vidan, Laia; Thomas, Christopher; Sassoon, Isabel; McGurk, Mark; Fenlon, Michael; Urbano, Teresa Guerrero
Abstract: Objectives: This observational study aims to determine individual dental doses in oropharyngeal cancer (OPC) patients managed by intensity modulated radiation treatment (IMRT). Materials and methods: OPC patients treated with IMRT had each tooth individually contoured on post‐IMRT CT scans. The mean, maximum and minimum doses were calculated per tooth‐based upon patient and tumor demographics (tumor size and nodal status). Results: A total of 160 patients were included in this study. Escalating tumor size and nodal status led to an observed increase in Dmean doses to the dentition on the contralateral tumor side. A significant region in both jaws received >30 Gy in this tumor group. Conclusion: Tumor demographics were observed to influence RT doses to the dentition and need to be considered when providing a pre‐RT dental assessment. The observed dose of >30 Gy in large spans of the dentition and jaws highlights future risk of dental deterioration and ORN with long term survival.